Analisis Fungsi Kesatuan Penjagaan Laut dan Pantai (KPLP)/Indonesia Sea And Coast Guard Guna Penegakan Hukum Pelayaran di Daerah Lingkungan Kerja dan Daerah Lingkungan Kepentingan Pelabuhan Tanjung Mas Semarang - Winarno; Romanda Annas Amrullah (Dinamika Bahari, 2020)
In the administration of President Jokowi Widodo has established a national maritime policy through the concept of Indonesia as a World Maritime Axis (PMD). This concept was conveyed by President Jokowi Widodo at the 9th East Asia Summit (EAS), 13 November 2014. Maritime security is not only the main task of the Navy as the main backbone of a country's maritime security, but cannot be separated from the support of non-military (civilian) agencies whose duties and functions are closely attached to the aspects of maritime security and safety surveillance, in this case, the Coast. Guard (Coast Guard). This research is qualitative research and uses descriptive analysis aimed at describing the tasks and problems faced by the Sea and Coast Guard Unit as a Sea and Coast Guard in the Work Environment Area (DLKr) and the Environmental Interest Area (DLKp) Tanjung Mas Port Semarang, as well as relating to the policies taken by KSOP Tanjung Mas Semarang in overcoming problems that arise in the field related to KPLP functions based on Law Number 17 of 2008 concerning Shipping.